2021
DOI: 10.3389/fmicb.2021.621719
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Sequencing for the Detection and Characterization of RNA Viruses

Abstract: This review aims to assess and recommend approaches for targeted and agnostic High Throughput Sequencing of RNA viruses in a variety of sample matrices. HTS also referred to as deep sequencing, next generation sequencing and third generation sequencing; has much to offer to the field of environmental virology as its increased sequencing depth circumvents issues with cloning environmental isolates for Sanger sequencing. That said however, it is important to consider the challenges and biases that method choice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 172 publications
(132 reference statements)
0
49
0
Order By: Relevance
“…2 c). Sequencing technologies are now capable of identifying both DNA and RNA viruses [104] , [43] . Nonetheless, the diversity of capsid architectures among viruses different than tailed phages is smaller [89] .…”
Section: Discussionmentioning
confidence: 99%
“…2 c). Sequencing technologies are now capable of identifying both DNA and RNA viruses [104] , [43] . Nonetheless, the diversity of capsid architectures among viruses different than tailed phages is smaller [89] .…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment strategies are often needed to increase the sensitivity of NGS approaches ( Lewandowski et al. 2019 ; Fitzpatrick et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, rotaviral opportunities for inter and intra-viral family recombination are enhanced through environmental persistence, factors that promote the emergence of genetic variants with increased capacity to cause large scale outbreaks. 147 When in air and on fomites under the conditions of high humidity, studies have shown that they can persist for hours without losing their infectivity. 148 Although RV diseases are universally distributed, the epidemiological characteristics vary in different climatic regions.…”
Section: Survival and Factors Influencing Viral Persistence In The Aq...mentioning
confidence: 99%